Study on reaction rates for 2T SF6 plasma: application to chemical kinetics of a decaying arc in high voltage circuit breakers. (May 2019) - Baumann, X; Teulet, Ph; Cressault, Y; Bultel, A
Abstract: This work is devoted to the study and comparison of theories to calculate densities of chemical species in a SF6 plasma in thermal non equilibrium conditions. The limits of the 2T law of mass action are shown. Then, the reaction rates are studied for several types of processes and they are implemented in a chemical kinetic model to acess the composition of the plasma. Finally, a comparison with the densities obtained with the law of mass action is performed and the results are discussed.